Interregional Payments Compared with International Payments - Hartland, Penelope (Quarterly Journal of Economics, 1949)
I. Interregional trade in the United States, 392. — II. Traditional explanations, 393. — III. Payments data for the United States, 396. — IV. The role of Treasury transfers, 400. — V. Summary, 407.